EFFECT OF ACORUS CALAMUS LINN ON ASTROCYTES IN THE SUBGRANULAR ZONE OF THE DENTATE GYRUS IN THE HIPPOCAMPAL REGION IS NEUROPROTECTIVE. - Dr.Subamalani S; Dr.Sasikumar Arumugam; Dr.Balaji Arumugam; Dr. Jamunarani Srirangaramasamy (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Our objective was to examine and uncover the neuroprotective properties of the plant Acorus calamus linn, also referred to as Vacha. Any form of stress is a major contributing factor to a number of ailments. In the future, a medication molecule with the ability to minimize cellular damage, boost antioxidant levels, and combat stress will be required. Thus, a total of 24 male Wistar albino rats—that is, 6 groups of animals—were used in the current investigation. Dimethyl sulphoxide (1 mL/kg/p.o./day) was given as a control. Stress: administered 1 mL/kg/p.o./day of dimethyl sulphoxide and underwent 6 hours of restraint per day. EE-ACL: Mammals ACL ethanolic extract (100 mg/kg/p.o./day) was received. Alpha-asarone (9 mg/kg/p.o/day) was administered 30 minutes prior to undergoing 21 days of restraint stress. Sigma Plot 13.0 was utilized for data analysis. According to the findings, rats given an ethanolic extract of Acorus calemus Linn and active principle alpha-asarone prior to stress demonstrated noticeably better spontaneous alteration behavior in the Y maze test. Additionally, the drug-treated groups’ corticosterone levels were lower than those of the stress group. The amount of neurons in the dentate gyrus region of the hippocampal regions in drug-treated groups remained comparable to those in the control group, as indicated by toludine blue staining. In the drug-treated groups, glial fibrillic acidic protein immunoreactivity revealed newly proliferating astrocytes that looked like stars. The fibers were thin and had a regular course. The findings imply that the central nervous system is produced by phytochemicals, specifically those found in polyphenolic compounds, glycosides, flavonoids, alkaloids, and triterpenoids, have a relaxing effect . The rhizome of Acorus calamus linn, which is rich in these phytochemicals, effectively reversed changes brought on by stress by reducing neuroinflammation and enhancing cognitive function